Dinitrogen functionalization at a ditantalum center. Balancing N2 displacement and N2 functionalization in the reaction of coordinated N2 with CS2. Issue 24 (5th June 2018) - Burford, Richard J.; Castro, Ludovic; Maron, Laurent; Hein, Jason E.; Fryzuk, Michael D.
Abstract : The reaction of CS2 with the side-on end-on dinitrogen complex ([NPN Si ]Ta)2 (μ–η 1 :η 2 -N2 )(μ-H)2 generates two products, the ratio of which depends on the concentration of added CS2 . Abstract : The reaction of carbon disulfide (CS2 ) with the side-on end-on dinitrogen complex ([NPN Si ]Ta)2 (μ–η 1 :η 2 -N2 )(μ-H)2 (1 ) (where [NPN Si ] = [PhP(CH2 SiMe2 NPh)2 ]) has been studied and shown to generate two products, the ratio of which depends on the concentration of added carbon disulfide. At high concentrations of CS2, N–N bond cleavage and functionalization occur to generate a ditantalum complex with an isothiocyanato ligand N-bound to Ta along with bridging sulfido and nitrido moieties. At lower concentrations of CS2, less dinitrogen functionalization is observed; instead, N2 is displaced and the CS2 molecule is completely disassembled to generate a ditantalum derivative with bridging methylene and two sulfide moieties. Kinetic and DFT studies have been performed and provide clues about the product ratio and mechanistic information and shed light on why N2 functionalization is challenging.